2023
DOI: 10.30574/wjarr.2023.20.2.2243
|View full text |Cite
|
Sign up to set email alerts
|

Identification of benefits from Integrated Management Systems (IMS) to achieve Sustainability: A Systematic Literature Review

Kazi Humayra Shams,
Subrata Talapatra,
Fardeen Islam
et al.

Abstract: In the pursuit of sustainable development within Bangladesh's Readymade Garment (RMG) sector, this study undertakes an analysis of the substantial advantages of deploying an Integrated Management System (IMS). Focusing on ISO 9001:2015, ISO 14001:2015, OSHAS 18001:2007, and SA 8000:2014, the research illuminates the pivotal role of IMS in the context of this vital industry. The research methodology involved searching Google Scholar, Emerald, and Elsevier databases for IMS benefits from 2005 to 2022. Key IMS ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Similarly, Ispas et al (2023) also highlight the same interpretation in study. The study showed that if a firm adopts to the IMS standards, it improves their relations with the supplier (Kazi Humayra Shams et al, 2023). This in turn increased the supply chain effectiveness and promoted the sales and export performance.…”
Section: The Effect Of Ims Adoption On the Export Performance Of Firmsmentioning
confidence: 96%
“…Similarly, Ispas et al (2023) also highlight the same interpretation in study. The study showed that if a firm adopts to the IMS standards, it improves their relations with the supplier (Kazi Humayra Shams et al, 2023). This in turn increased the supply chain effectiveness and promoted the sales and export performance.…”
Section: The Effect Of Ims Adoption On the Export Performance Of Firmsmentioning
confidence: 96%